2017
DOI: 10.4274/tjo.52138
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Molluscum Contagiosum Lesions in Two Patients with Unilateral Chronic Conjunctivitis

Abstract: Molluscum contagiosum (MC) is a viral infection of the skin and mucosal tissues characterized by skin-colored or transparent round nodules with a dimple or pit in the center. The infection is caused by a DNA poxvirus called the MC virus. Although MC generally occurs in children, it has also been reported in immunocompromised and atopic patients. The virus is transmitted by skin contact or sexual intercourse. The lesions disappear spontaneously within several months in most cases. However, excision, cryotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
0
15
0
5
Order By: Relevance
“…In this case, lesions are typically located on the scalp and have a circular arrangement 38. Other sites of atypical location,1 in addition to the oral mucosa, include the palms and soles, the areola/nipple,39,40 the conjunctiva,41 lips,42 eyelids,43 among others 44. Clinical presentation of periocular lesions has been described as erythematous, nodular umbilicated, big/giant, conglomerated, inflamed, or pedunculated 45.…”
Section: Clinical Manifestationsmentioning
confidence: 96%
“…In this case, lesions are typically located on the scalp and have a circular arrangement 38. Other sites of atypical location,1 in addition to the oral mucosa, include the palms and soles, the areola/nipple,39,40 the conjunctiva,41 lips,42 eyelids,43 among others 44. Clinical presentation of periocular lesions has been described as erythematous, nodular umbilicated, big/giant, conglomerated, inflamed, or pedunculated 45.…”
Section: Clinical Manifestationsmentioning
confidence: 96%
“…It is likely for the primary eye care providers to miss the cutaneous lesions and continue to treat the associated congestion of the conjunctiva as allergic conjunctivitis as demonstrated in our case report. [26] Schornack et al observed that in almost 40% of cases, OMC were not diagnosed in the first visit. [4] Primary skin care providers in their turn need to be aware that MC lesions near the eye may trigger anterior segment inflammation presenting most commonly as unilateral chronic conjunctivitis.…”
Section: Discussionmentioning
confidence: 99%
“…Serin et al and Balakrishnan et al have reported immediate resolution of conjunctivitis as well as keratitis with excision of primary MC lesions around the eyelid. [26] However, surgical or chemical ablative therapies in a periorbital location risks infection and scarring especially in pediatric or immune compromised patients. [2] Cidofovir and Brincidofovir, a broad spectrum lipid conjugate of cidofovir, have been shown to be efficacious in MC lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may occur less commonly in other sites of skin and mucosa including oral cavity and eyelids. [ 1 2 3 ] They can occur on the scalp along with lesions on other sites but lesions localized only to the scalp is quite infrequent. [ 4 5 ] However, lesions over scalp have been described in the past in a newborn[ 6 ] and in children[ 7 8 ] Cases of isolated lesions on the scalp of an adult by Hill and Messina[ 9 ] have been reported in the past in the western literature.…”
mentioning
confidence: 99%